Open electromagnetic waveguides - Rozzi, T. (Tullio); Mongiardo, M. (Mauro) (Institution of Engineering and Technology, 1997)
This book is aimed at providing an extensive introduction to the practical use of spectral methods in solving real engineering problems in open electromagnetic waveguide environment. It is meant equally for the benefit of researchers in microwave and millimetric wave components as for its use as a textbook in specialistic courses. It consists of eight chapters: introduction to open electromagnetic waveguides; electromagnetic theory; planar dielectric waveguides; bound modes by approximate methods; discontinuities in planar dielectric waveguides; bound modes by transverse resonance diffraction; complete spectra of open waveguides; and examples and applications.